Evaluating the effects of beach nourishment on littoral morphodynamics at kuala nerus, terengganu (Malaysia) - Ariffin, E.H. (Universiti Malaysia Terengganu, 2020)
Since 2008, Kuala Nerus has undergone rapid urbanization along its coastline, resulting in the loss of sand along the littoral zone. Due to the heavy erosion in 2012 at Tok Jembal beach that migrated to Universiti Malaysia Terengganu (UMT) beach in 2013, the Department of Irrigation and Drainage has implemented a coastal defence project to mitigate erosion by building a series of ripraps/revetments along the coasts. Additionally, breakwaters and groyne structures were built in combination with beach nourishment programme. For the sustenance of the local fishermen community, the Malaysia Public Works Department replaced one of the breakwaters to a jetty-type breakwater at Tok Jembal beach. Shoreline evaluations, beach profile measurements and numerical modelling were used in this present study to identify the effectiveness of combining the coastal defence and beach nourishment programmes. The combination of programmes successfully initiated the accretion of a ~30 m beach dune and created new beaches. However, erosion remains persistent in the beach that was unprotected and exposed directly to the South China Sea. We posit that a combination of coastal defence and beach nourishment programmes can potentially interrupt dynamic coastal processes, especially the current parameters. Â© Penerbit UMT.